Teknologi Printer 3D untuk Meningkatkan Kreativitas Guru Sekolah dalam Pembentukan Prototipe Media Pembelajaran (Universitas Negeri Padang, 2020)
Learning media for Vocational High School students provides deeper understanding toward a subject in the class. Since that, the teachers need to find some ideas in terms of creation real objects for their pupils. The 3D printing technology capable to deliver the requirements in constructing prototype objects for disciples. In this study, Fused Deposition Modelling (FDM) model chosen to build 3D printer with PLA filament material. The microcontroller SKR V1.3 mounted inside the machine as main board to control the operational of device. With a fine level of precision, the printing result shows good geometry and object dimension to create some objects. The conclusion could be drawn are the 3D printer has capability to create prototype objects, and with spend low cost the device is good alternative way for teachers to present their realistic media for disciples.